Answer:
Step-by-step explanation:
just simplify the LHS first.
You can either multiply 1/5 by (x+3) and then solve
or
multiply both sides by 5 to get rid of 1/5 on LHS
I will multiply by 5
(x+3)= -10x-15 ( 5*1/5(x+3)= -5(2x+3)
now rearrange the equation
x+3=-10x-15
-10x-15-x-3=0
-11x-17=0
-11x=17
x= -17/11
Answer:
False
Step-by-step explanation:
The people arent random
Answer: 0.000008
Step-by-step explanation:
So it says 10 to the -6 power...
10*-10*-10*-10*-10*-10*-10
0.000001
Then you multiply that by 8
0.000008
Hope this helps!